Astragalus Flavone Ameliorates Atherosclerosis and Hepatic Steatosis Via Inhibiting Lipid-Disorder and Inflammation in apoE−/− Mice - Ma, Chuanrui; Zhang, Jing; Yang, Shu; Hua, Yunqing; Su, Jing; Shang, Yuna; Wang, Zhongyan; Feng, Ke; Zhang, Jian; Yang, Xiaoxiao; Zhang, Hao; Mao, Jingyuan; et al. (Frontiers in Pharmacology, 2020)
Atherosclerosis is a major pathogenic driver of cardiovascular diseases. Foam cell formation plays a key role in atherogenesis, which is affected by lipid disorder and inflammation. Therefore, inhibition of foam cell formation is a therapeutic approach for atherosclerosis treatment. Total flavone of Astragalus membranaceus (TFA) is extracted from A. membranaceus that has protective effect on cardiovascular disease. However, the effect of TFA on atherosclerosis and the underlying mechanism remains unknown. In this study, we determined whether TFA could inhibit atherosclerosis and uncovered the underlying mechanism. In vivo, ApoE deficient mice were treated with TFA and high-fat diet for 16 weeks. Subsequently, atherosclerotic lesions, hepatic steatosis and associated genes expression in vitro and in vivo were determined. We found that TFA reduced atherosclerotic lesion size and enhanced plaque stability, which might be attributed to improved lipid disorder, reduced inflammation and decreased monocyte adhesion. Mechanistically, TFA inhibited hepatic steatosis via regulating the genes responsible for lipid metabolism, by which ameliorating the lipid disorder. Moreover, in macrophage, TFA reduced the expression of scavenger receptors such as CD36 and SRA; and promoted the expression of ATP-binding cassette transporter A1 and G1 (ABCA1/G1). More importantly, TFA reduced miR-33 expression and dampened NFκB activity, by which de-repressing ABCA1/G1 activity and inhibiting the inflammation. Collectively, TFA can attenuate atherosclerosis via dual suppression of miR-33 and NFκB pathway, and partially through inhibition of scavenger receptors in macrophage. In addition, TFA ameliorates the hepatic steatosis and lipid disorder, which in turn contributes to the amelioration of atherosclerosis, suggesting that TFA might be a novel therapeutic approach for inhibition of atherosclerosis and hepatic steatosis.